Creativity and Mental Imagery - Raffaella Nori (Frontiers Research Topics, 2016)
Creativity is increasingly attracting attention of scientific community given its role in different aspects of human life. So far we have only began to understand its complexity and how it correlates with other cognitive processes. A further understanding of its key processes is essential to better implement applications of creativity tools to daily life. Therefore, it is the aim of this Research Topics to further elucidate how creativity can be measured, and its components, such as mental imagery, are determined.